Upregulation of cyclin-dependent kinase inhibitors CDKN1B and CDKN1C in hepatocellular carcinoma-derived cells via goniothalamin-mediated protein stabilization and epigenetic modifications. (2015) - Peng, Yu-Ting; Wu, Wen-Ren; Chen, Lih-Ren; Kuo, Kung-Kai; Tsai, Cheng-Hui; Huang, Yu-Ting; Lan, Yu-Hsuan; Chang, Fang-Rong; Wu, Yang-Chang; Shiue, Yow-Ling
Abstract: Cell cycle deregulation is common in human hepatocellular carcinoma (HCC). To ensure proper cell cycle controlling, cyclin/cyclin-dependent kinases (CDK) complexes are tightly regulated by CDK inhibitors (CKIs) in normal cells. However, insufficient cyclin-dependent kinase inhibitor 1B (CDKN1B, also known as p27 Kip1 ) and CDKN1C (p57 Kip2 ) proteins are characteristics of high-risk HCC. In two HCC-derived cell lines with distinct genetic backgrounds, we identified a small natural compound, goniothalamin (GTN), serving as an inducer of CKIs. In TP53-mutated (Y220C) and retinoblastoma 1 (RB1)-positive Huh-7 cells, GTN stabilized CDKN1B protein levels by targeting the degradation of its specific E3 ubiquitin ligase (S-phase kinase-associated protein 2). Alternatively, in TP53- and RB1-negative Hep-3B cells, GTN increased CDKN1C transcription and its subsequent translation by acting as a histone deacetylase inhibitor. In both cell lines, GTN induced G0 /G1 cell cycle arrest, delayed S phase entry of cells and inhibited anchorage-independent cell growth which might be attributed to the upregulation of CKIs and downregulation of several positive cell cycle regulators, including CDC28 protein kinase regulator subunit 1B, cyclin E1 and D1, cyclin-dependent kinase 2 (CDK2), CDK4, CDK6, E2F transcription factor 1 and/or transcription factor Dp-1. Therefore, GTN might represent a novel class of anticancer drug that induces CKIs through post-translational and epigenetic modifications.